Everybody matters The extraordinary power of caring for your people like family - Chapman, Bob. (Dreamscape, 2015)
In 1997, Bob Chapman and Barry-Wehmiller pioneered a dramatically different approach to leadership that creates off-the-charts morale, loyalty, creativity, and business performance. They utterly rejected the idea that employees are simply functions to be moved around, "managed" with carrots and sticks, or discarded at will. Instead, their company, Barry-Wehmiller, manifested the reality that every single person matters, just like in a family―and that understanding of how employees should be thought of and treated has remained the bedrock of their company?s success. Chapman and his coauthor Raj Sisodia show how any organization can enact this type of leadership, providing clear steps to transform your own workplace, whether you lead two people or two hundred thousand.
Keywords: Leadership